Gender, Race and Class Dimensions of Nonstandard Work - Zeytinoglu, Isik; Muteshi, Jacinta (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
This review article critically analyzes and synthesizes the academic literature on nonstandard work and its gender, race and class dimensions. We argue that it is important and crucial to understand these dimensions of nonstandard work in order to develop appropriate labour policies. We present our discussion in a conceptual framework of duality within which nonstandard workforms are located. We discuss the role the unions could play in achieving equity in labour markets and conclude the paper with recommended labour policy changes to respond to the needs of women, particularly those racial minority and low economic class women employed in nonstandard jobs.